(3JGL GddZI hUMGM GdYQHjIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s
(3ChdgG (B:s
(3HGH GddGe , aUd GdCda (B: (3CHd (B: (3GdEHd dG hGMO dgG ef daXgG , hgj eDfKI , dGf CSeGA GdLehY GdJi dG hGMO dgG ef daXgG EPG cGfJ dZjQ GdBejjf s
(3GdcQGSI GdChdi HNW eZGjQ LjOs
(3dYdg ef NWhW GdbQf GdJGSY GdgLQi hcQGSI ai GdhSW HNW MOjKs
(3GdfSNI HgG MhGTs
(3HChdgG Jedc eDQN SfI (B894 (3hjJab BNQgG eY BNQ fSNI YGQa MceJ (B28 - (3dZI s
(3HgG fXGe GdJYbjHI s
(3fSNI QGHYI YTQI s
Keywords: (3GddZIs